2020
DOI: 10.1186/s12951-020-00722-2
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastases-derived extracellular vesicles induce binding and aggregation of low-density lipoprotein

Abstract: Background Cancer cell-derived extracellular vesicles (EVs) have previously been shown to contribute to pre-metastatic niche formation. Specifically, aggressive tumors secrete pro-metastatic EVs that travel in the circulation to distant organs to modulate the microenvironment for future metastatic spread. Previous studies have focused on the interface between pro-metastatic EVs and epithelial/endothelial cells in the pre-metastatic niche. However, EV interactions with circulating components suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 83 publications
5
71
0
Order By: Relevance
“…EVs were separated from other medium components through tangential flow filtration. Consistent with previously published studies [ 45 , 46 , 65 ], tangential flow filtration resulted in separation and concentration of nanosized EVs ( Figure 1 b, Supplementary Figure S1 ) that exhibited a negative zeta potential as expected ( Figure 1 c). Isolated EVs contained Hsc70, annexin V, CD63, and CD9 ( Figure 1 d), which are characteristic markers [ 12 ] and were negative for calnexin, an endoplasmic reticulum protein ( Figure 1 d) typically used as an indicator of intracellular vesicle contaminants [ 12 ].…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…EVs were separated from other medium components through tangential flow filtration. Consistent with previously published studies [ 45 , 46 , 65 ], tangential flow filtration resulted in separation and concentration of nanosized EVs ( Figure 1 b, Supplementary Figure S1 ) that exhibited a negative zeta potential as expected ( Figure 1 c). Isolated EVs contained Hsc70, annexin V, CD63, and CD9 ( Figure 1 d), which are characteristic markers [ 12 ] and were negative for calnexin, an endoplasmic reticulum protein ( Figure 1 d) typically used as an indicator of intracellular vesicle contaminants [ 12 ].…”
Section: Resultssupporting
confidence: 91%
“…Such agents could potentially exhibit tumorigenicity or lead to accelerated growth of existing tumors. Additionally, EVs from cancer cells may display abnormal interactions with circulating components [ 65 ]. Despite the potential safety concerns of cancer cell-derived EVs, several initial clinical trials have demonstrated that such EVs have acceptable safety profiles [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations